Pre-treatment by n-hexane extract of Phyllanthus niruri can alleviate paracetamol-induced damage of the rat liver - Md. Jalaluddin Iqbal, Fawzia Z. Dewan, S.A.R.Chowdhury, M.I.R. Mamun (Bangladesh Pharmacological Society, 2007)
The present study aimed to obtain and evaluate remedy against viral hepatitis with Phyllanthus niruri (Bhui amla). Viral infection and toxic doses of paracetamol produce similar pattern of hepatotoxicity. Hepatotoxicity was induced by administering paracetamol (750 mg/kg body weight, single dose intraperitoneal) into one group (group P) of rats. Propylene glycol (vehicle) was administered (2 ml) into another group (group V) of rats. Four groups of P. niruri extract-pretreated (200 mg/kg body weight/day for 7 days) rats were administered the same single dose of paracetamol on the 7th day. Extract of P. niruri were obtained through ethanol (E), hexane (H), dichloromethane (D) and butane (B). Rat groups were V, P, E + P, H + P, D + P and B + P. Each group consisted of 6 rats and were sacrificed on the 9th day. Parameters for evaluation were biochemical (serum ALT, serum AST, serum ALP, serum bilirubin), hepatic reduced glutathione concentrations and hepatic histology. Propylene glycol (group V) appeared non-toxic to the liver while significant degrees of centrilobuler hepatotoxicity was observed in group P paracetamol-treated rats. The E + P group suggested significant improvements in the serum parameters but these parameters appeared better alleviated in the H + P group. Hepatic reduced glutathione concentrations were replenished to the control level in both E + P and H + P groups. Hepatic histology supported biochemical and other observations in the P, E + P and H + P groups. Lesser degrees of alleviations were observed in the D + P and B + P groups. However, the hexane extract-pretreated group (H + P) appeared to provide the most significant hepatoprotection against paracetamol induced hepatotoxicity in the rat. Titration of the dose following isolation of the active ingredient might offer complete alleviation.